Bacterial diversity in typical abandoned multi-contaminated nonferrous metal(loid) tailings during natural attenuation. (April 2019) - Liu, Jian-li; Yao, Jun; Wang, Fei; Min, Ning; Gu, Ji-hai; Li, Zi-fu; Sunahara, Geoffrey; Duran, Robert; Solevic-Knudsen, Tatjana; Hudson-Edwards, Karen A.; Alakangas, Lena
Abstract: Abandoned nonferrous metal(loid) tailings sites are anthropogenic, and represent unique and extreme ecological niches for microbial communities. Tailings contain elevated and toxic content of metal(loid)s that had negative effects on local human health and regional ecosystems. Microbial communities in these typical tailings undergoing natural attenuation are often very poorly examined. The diversity and inferred functions of bacterial communities were examined at seven nonferrous metal(loid) tailings sites in Guangxi (China), which were abandoned between 3 and 31 years ago. The acidity of the tailings sites rose over 31 years of site inactivity. Desulfurivibrio, which were always coupled with sulfur/sulfide oxidation to dissimilate the reduction of nitrate/nitrite, were specific in tailings with 3 years abandonment. However, genus beneficial to plant growth ( Rhizobium ), and iron/sulfur-oxidizing bacteria and metal(loid)-related genera ( Acidiferrobacter and Acidithiobacillus ) were specific within tailings abandoned for 23 years or more. The increased abundance of acid-generating iron/sulfur-oxidizing and metal(loid)-related bacteria and specific bacterial communities during the natural attenuation could provide new insights for understanding microbial ecosystem functioning in mine tailings. OTUs related to Sulfuriferula, Bacillus, Sulfurifustis, Gaiella, and Thiobacillus genera were the main contributors differentiating the bacterial communities between the different tailing sites. Multiple correlation analyses between bacterial communities and geochemical parameters indicated that pH, TOC, TN, As, Pb, and Cu were the main drivers influencing the bacterial community structures. PICRUSt functional exploration revealed that the main functions were related to DNA repair and recombination, important functions for bacterial adaptation to cope with the multi-contamination of tailings. Such information provides new insights to guide future metagenomic studies for the identification of key functions beyond metal-transformation/resistance. As well, our results offers novel outlooks for the management of bacterial communities during natural attenuation of multi-contaminated nonferrous metal(loid) tailings sites. Graphical abstract: Image 1 Highlights: Specific bacterial communities were observed according to tailing age. S/Fe-oxidizing and metal(loid)-related bacteria abundance increased with tailings age. Genera beneficial to plant growth were detected. Bacterial communities harbored adaptive DNA repair and recombination functions.